2021
DOI: 10.1002/ird.2564
|View full text |Cite
|
Sign up to set email alerts
|

DRAINMOD simulation of paddy field drainage strategies and adaptation to future climate change in lower reaches of the Yangtze river basin*

Abstract: The DRAINMOD model was used to simulate the current and future water balance in the Yanyun Irrigation District, China. Projections of future climate in the district (2021:2050) show that annual maximum and minimum temperatures will increase by [1.09 and 1.15 °C] under the representative concentration pathway RCP4.5 and [1.34 and 1.39 °C] under RCP8.5, besides more frequency of one‐day peak precipitation events. DRAINMOD simulations revealed that future annual runoff will increase by 33.3% (RCP4.5) and 36.9% (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This could cause the model to produce improper predictions of the farmland water balance during the periods of mid-summer drainage practices (when the surface depression capacity varies due to agricultural practices). To assess such a problem, we review the results of the study conducted by Awad et al [15], who applied the DRAINMOD model to predict the water fate in a paddy area that has mid-summer drainage practices. We aim to focus on the period during which the surface depression capacity changes.…”
Section: Effect Of Surface Depression Capacitymentioning
confidence: 99%
See 3 more Smart Citations
“…This could cause the model to produce improper predictions of the farmland water balance during the periods of mid-summer drainage practices (when the surface depression capacity varies due to agricultural practices). To assess such a problem, we review the results of the study conducted by Awad et al [15], who applied the DRAINMOD model to predict the water fate in a paddy area that has mid-summer drainage practices. We aim to focus on the period during which the surface depression capacity changes.…”
Section: Effect Of Surface Depression Capacitymentioning
confidence: 99%
“…So, there is no option in the model to consider any changes in the capacity of surface depression (such as under mid-summer drainage practices). Since the surface depression capacity is a major determinant of the water fate in farmlands [15,16], the DRAINMOD model's shortage in considering changes in the surface depression capacity may cause the model to produce improper water distribution patterns in agricultural lands. Therefore, this paper reviews the DRAINMOD model's performance in the study conducted by Awad et al [15], who applied the model to predict Among all known methodologies and approaches for assessing the performance of subsurface drainage systems, mathematical models are superior since they save costs and time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If fertilizers are applied incorrectly, there is a signi cant risk that they will contaminate groundwater in waterlogged areas where groundwater tables are high enough to reach the topsoil layers, drastically reducing water quality (Ashraf et al, 2019; Srivastav, 2020 and Abd-Elaty et al, 2020). Numerous studies have suggested that farmlands with shallow water tables are more vulnerable to groundwater contamination (Awad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%